Energy Scheduling of Battery Storage Systems in Micro Grids - Armstorfer, Andreas; Biechl, Helmuth; Rosin, Argo (Electrical, Control and Communication Engineering, 2017)
Microgrids in island mode with high penetration of renewable energy sources in combination with gensets and battery storage systems need a control system for voltage and frequency. In this study the main goal is maximization of the energy feed-in by renewable sources. Therefore it is necessary to keep the State of Energy for the Battery Storage System in a range that the excess energy can be absorbed and used in a later period of the day. In this paper an approach for State of Charge scheduling based on load and generation prediction is described.